Methane production by three widespread marine phytoplankton species: release rates, precursor compounds, and potential relevance for the environment - Klintzsch, Thomas; Langer, Gerald; Nehrke, Gernot; Wieland, Anna; Lenhart, Katharina; Keppler, Frank (Biogeosciences, 2019)
Abstract. Methane (CH4) production within the oceanic mixed layer is a widespread phenomenon, but the underlying mechanisms are still under debate. Marine algae might contribute to the observed CH4 oversaturation in oxic waters, but so far direct evidence for CH4 production by marine algae has only been provided for the coccolithophore Emiliania huxleyi. In the present study we investigated, next to E. huxleyi, other widespread haptophytes, i.e., Phaeocystis globosa and Chrysochromulina sp. We performed CH4 production and stable carbon isotope measurements and provide unambiguous evidence that all three investigated marine algae are involved in the production of CH4 under oxic conditions. Rates ranged from 1.9±0.6 to 3.1±0.4 µg of CH4 per gram of POC (particulate organic carbon) per day, with Chrysochromulina sp. and E. huxleyi showing the lowest and highest rates, respectively. Cellular CH4 production rates ranged from 16.8±6.5 (P. globosa) to 62.3±6.4 ag CH4 cell−1 d−1 (E. huxleyi; ag = 10−18 g). In cultures that were treated with 13C-labeled hydrogen carbonate, δ13CH4 values increased with incubation time, resulting from the conversion of 13C-hydrogen carbonate to 13CH4. The addition of 13C-labeled dimethyl sulfide, dimethyl sulfoxide, and methionine sulfoxide - known algal metabolites that are ubiquitous in marine surface layers - resulted in the occurrence of 13C-enriched CH4 in cultures of E. huxleyi, clearly indicating that methylated sulfur compounds are also precursors of CH4. By comparing the algal CH4 production rates from our laboratory experiments with results previously reported in two field studies of the Pacific Ocean and the Baltic Sea, we might conclude that algae-mediated CH4 release is contributing to CH4 oversaturation in oxic waters. Therefore, we propose that haptophyte mediated CH4 production could be a common and important process in marine surface waters.
Gesehen am 31.10.2019